COMBINATION OF BABY MASSAGE AND CITRONELLA AROMATHERAPY ON WEIGHT INCREASE IN TODDLERS AGED 12-13 MONTHS: QUASI EXPERIMENTAL - Meika Jaya Rochkmana; Meilia Nindya Zulis Windyarti; Samrotul Fuadah Fuadah (Jurnal Smart Kebidanan, 2025)
Malnutrition in children is caused by multifactors so that it requires immediate treatment to prevent further complications. One effort to increase nutritional intake in toddlers is baby massage and Citronella aromatherapy. The purpose of this study was to determine the effectiveness of the combination of baby massage and citronella aromatherapy on increasing body weight in malnourished toddlers aged 12-23 months. The type of research is quasi-experimental with one group pretest posttest design. The sample was 50 malnourished toddlers aged 12-23 months. The sampling technique was purposive sampling. The research instruments were weight observation sheets, citronella oil and SOP. The action of giving baby massage and lemongrass aroma simultaneously through inhalation, given twice a week in the afternoon for 4 weeks. 3 drops of Aromatherapy in 400 ml of water using a diffuser for 15 minutes. Baby massage is given for 15 minutes. The weight of malnourished toddlers aged 12-23 months before the intervention was given an average of 7.346 kg and after the intervention was given 7.678 kg. Combination of baby massage and citronella aromatherapy had an effect on increasing the weight of malnourished toddlers. Mothers of malnourished toddlers can provide a combination of baby massage and citronella aromatherapy to increase weight and catch up on their toddlers' growth delays.